Novel-Selective Bromazepam Membrane Sensors: Application Pharmaceutical Preparations and Biological Fluids - El-Tohamy, Maha; Razeq, Sawsan; A. Shalaby, Abdalla (Asian Journal of Chemistry, 2011)
The construction and performance characteristics of bromazepam selective electrodes were developed. Two types of electrodes: plastic membrane I and coated wire II were constructed based on the incorporation of bromazepam with phosphomolybdic acid. The influence of membrane composition, kind of plasticizer, pH of the test solution, soaking time and foreign ions on the electrodes was investigated. The electrodes showed a Nernstian response with a mean calibration graph slope of 53.22 ± 0.7 and 51.63 ± 0.4 mV decade-1 at 25 ºC for electrode I and II, respectively, over bromazepam concentration range from 5.0 × 10-6 to 1.0 × 10-3 and 1.0 × 10-6 to 1.0 × 10-3 mol L-1, with detection limit 2.5 × 10-6 mol L-1 and 5.01 × 10-7 mol L-1 for electrode I and II, respectively. The constructed electrodes gave average selective precision and accuracy within the pH range 3-8. Interferences from common cations, alkaloids, sugars, amino acids and drug excipients were reported. The results obtained by the proposed electrodes were also applied successfully to the determination of the drug in pharmaceutical preparations.